Introduction of spring-assisted cranioplasty for scaphocephaly in Russia: first cases evaluated using detailed craniometry and principal component analysis. Issue 3 (4th May 2019) - Satanin, Leonid; Teterin, Ivan; Evteev, Andrey; Sakharov, Alexander; Kölby, Lars; Lemeneva, Natalia; Roginsky, Vitaly
Abstract: Spring-assisted cranioplasty (SAC) was recently introduced in Moscow. This study provides a detailed analysis of the results of the first 14 SAC cases in Russia. The patients underwent a computed tomography scan before surgery and prior to spring removal 3 months later. Fourteen cases (10 males and 4 females) were operated on, with a mean surgery time of 56 ± 14 min. All operations were uneventful, with a mean hospital stay of 4.2 days. Detailed craniometry of the 10 male patients and their matched controls revealed that SAC induced changes in the shape of the entire skull. The cranial index of the male patients increased from 68.2 to 72.3, whereas it remained stable at ∼80 for the controls. The anterior and middle skull heights were significantly larger in cases as compared with controls but shifted toward normal levels following SAC. Additionally, SAC increased parietal bone curvature, and principal component analysis showed that post-SAC morphological changes in patients were comparable to normal growth changes in the skull morphology of the controls. However, several months after the operation, patients continued to display a clearly distinct cranial morphology as compared with that of controls. These results indicated that SAC is a safe technique that showed good surgical results immediately after introduction.